Memaksimalkan Peran Guru dalam Meningkatkan Disiplin Belajar Siswa Sekolah Dasar - Zaleha, Zaleha (Yayasan Sembilan Pemuda Indonesia, 2021)
The purpose of this study was to determine the teacher's efforts to improve student learning discipline during the pandemic by maximizing the role of the teacher. This research was conducted at SD Negeri 34 Prabumulih. Data collection techniques using interviews, observation, and documentation. After that, the data can be summarized or collected and analyzed through three stages of activity simultaneously, namely: data reduction, and concluding / verification. According to the findings of the study, the teacher's efforts to strengthen the learning discipline of SD Negeri 34 Prabumulih students by incorporating the values of the discipline into each topic presented so that discipline can become the students' basic character in everyday life. The teacher also creates conducive learning activities and an environment that encourages students to fully participate in the learning process. The instructor then continually develops his or her ability to handle learning by engaging in training and deepening his or her understanding of learning management by employing techniques/methods that apply to theory in authoritative publications related to learning management, both national and international journals.